2016
DOI: 10.1039/c6ra10869e
|View full text |Cite
|
Sign up to set email alerts
|

Optical detection of small biomolecule thiamines at a micromolar level by highly luminescent lanthanide complexes with tridentate N-heterocyclic ligands

Abstract: Based on the luminescence properties of lanthanide complexes, we found that very fast and extremely sensitive optical detection of thiamines can be achieved for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 43 publications
1
16
0
Order By: Relevance
“…Using lanthanide coordination compounds with organic ligands including aromatic moieties is one solution to this challenge. The inclusion of pyridyl and triazole moieties in organic molecules, for example, ensures efficient energy absorption, resulting in an increase in the luminescence of metal ions via indirect excitation [14][15][16][17][18][19] . In compounds with magnetically active metal ions, triazole bridges also mediate exchange coupling between paramagnetic centers via the M-N-N-M channels, which have short metal-nitrogen and nitrogen-nitrogen connections [20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…Using lanthanide coordination compounds with organic ligands including aromatic moieties is one solution to this challenge. The inclusion of pyridyl and triazole moieties in organic molecules, for example, ensures efficient energy absorption, resulting in an increase in the luminescence of metal ions via indirect excitation [14][15][16][17][18][19] . In compounds with magnetically active metal ions, triazole bridges also mediate exchange coupling between paramagnetic centers via the M-N-N-M channels, which have short metal-nitrogen and nitrogen-nitrogen connections [20][21][22][23][24] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, highly luminescent Ln III complexes ( Ln = Eu, Sm, Nd) with β‐diketone ligands were synthesized by Bassett et al Near‐IR luminescent ytterbium complexes with four Salen‐type ligands were reported . Du et al have reported a new series of Ln III complexes ( Ln = La, Ce, Pr, Nd, Sm, Eu, Gd, Tb) with tridentate N ‐heterocyclic ligand emitting strong luminescence with high efficiency . When aromatic carboxylic acids are served as organic ligands, lanthanide ions exhibit higher thermal or luminescent stability than other organic ligands for practical applications by virtue of their dimeric or infinite chain polymer structures .…”
Section: Introductionmentioning
confidence: 99%
“…7,8 In the meantime, lanthanide coordination polymers containing N-heterocyclic ligands show excellent luminescence by the antenna effect, in general, in which the N-heterocyclic ligand function is as a sensitizer. 9−11 In this aspect of the work, the ligand H 2 L {2,6-bis(5-methyl-1H-pyrazol-3-yl)pyridine} 12 was extensively investigated. Furthermore, the "-NH" in the H 2 L ligand (including pyrazole and pyridine) can act as Lewis base donors and Lewis acid acceptors in the same molecule.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Furthermore, the "-NH" in the H 2 L ligand (including pyrazole and pyridine) can act as Lewis base donors and Lewis acid acceptors in the same molecule. 9,12 Up to now, the crystal structures of some related compounds with 2,6-bis(5-methyl-1H-pyrazol-3-yl)pyridine (H 9,12 Although these molecules (tridentate N-heterocyclic ligand) can also serve as efficient antenna to sensitize the emission of lanthanide ions, exploration application studies about such kinds of coordination polymers are still quite limited.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation